A Literature Review on the Impact of Legal Reforms on Administrative Efficiency in Local Governments - Pramono, Wahyu; Hariadi, Berian; Mulia, Rizki Afri; Putri, Rianda Prima; Meilina, Susiyanti; Suryaningsih, Suryaningsih (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This research paper offers an extensive literature review concerning the effects of legal alterations on the operational efficiency of municipal administrations. Despite implementing numerous legislative modifications to improve administrative efficacy, many local governing bodies encounter obstacles such as bureaucratic procedures, corruption, and insufficient institutional capabilities. Successful instances in nations like South Korea and Singapore underscore the significance of digitalization within public administration and unwavering political dedication in overcoming these hindrances and bolstering transparency. Conversely, in regions such as India and various African countries, obstacles like institutional shortcomings and widespread corruption hinder the effectiveness of reform initiatives. Critical elements for the success of such reforms encompass institutional capacity, political backing, and the integration of information and communication technologies. Public involvement and the effective management of bureaucratic opposition are also paramount. This analysis furnishes valuable insights for policymakers and scholars aiming to devise and execute more effective legal reforms. Policy recommendations entail continual training for governmental officials, persistent political dedication, and customized strategies tailored to local reform implementation obstacles.